Histidine residue 252 of the Photosystem II D1 polypeptide is involved in a light-induced cross-linking of the polypeptide with the alpha subunit of cytochrome b-559: study of a site-directed mutant of Synechocystis PCC 6803 - Lupínková, Lenka; Metz, James G; Diner, Bruce A; Vass, Imre; Komenda, Josef (Biochimica et biophysica acta, 2002)
Properties of the Photosystem II (PSII) complex were examined in the wild-type (control) strain of the cyanobacterium Synechocystis PCC 6803 and its site-directed mutant D1-His252Leu in which the histidine residue 252 of the D1 polypeptide was replaced by leucine. This mutation caused a severe blockage of electron transfer between the PSII electron acceptors Q(A) and Q(B) and largely inhibited PSII oxygen evolving activity. Strong illumination induced formation of a D1-cytochrome b-559 adduct in isolated, detergent-solubilized thylakoid membranes from the control but not the mutant strain. The light-induced generation of the adduct was suppressed after prior modification of thylakoid proteins either with the histidine modifier platinum-terpyridine-chloride or with primary amino group modifiers. Anaerobic conditions and the presence of radical scavengers also inhibited the appearance of the adduct. The data suggest that the D1-cytochrome adduct is the product of a reaction between the oxidized residue His(252) of the D1 polypeptide and the N-terminal amino group of the cytochrome alpha subunit. As the rate of the D1 degradation in the control and mutant strains is similar, formation of the adduct does not seem to represent a required intermediary step in the D1 degradation pathway.
Keywords: Light; světlo; histidin; Amino Acid Sequence; Protein Subunits; podjednotky proteinů; Histidine; fotosyntetická reakční centra (proteinové komplexy); Photosystem II Protein Complex; Mutagenesis, Site-Directed; sinice; Cyanobacteria; molekulární sekvence - údaje; cytochromy typu b; Molecular Sequence Data; mutageneze cílená; sekvence aminokyselin; fotosystém II (proteinový komplex); Photosynthetic Reaction Center Complex Proteins; Cytochrome b Group